A Research on the Factors Affecting the Preference of Medical Specialization Branches - Öztürk, Nazife; Gençtürk, Mehmet (Journal of Medical Science, 2022)
Aim. The aim of this study is to determine the factors affecting the preferences of specialization in the field of medicine.Materials and Methods. Mixed research and exploratory sequential research design were used. In the exploratory phase, data were collected from specialist physicians (n=14) and findings were analyzed by descriptive and content analysis. In the light of qualitative findings, a measurement tool was developed and applied to medical school students and the physicians who prepared specialty exams (n = 502).Results. Qualitative findings were structured under 3 themes: individual, occupational and systemic factors. The measurement tool, which was named “Physicians' Preference Tendencies of Specialty Branch” was structured as 42 items and 7 dimensions: risk, comfort, health problems, status, emotional interest, gender, and marital status emerged.Conclusions. Although there are many factors that affect preferences of the medical field, it is concluded that personality traits and idealism of individuals and mortality rates associated with branch or field of medicine are the most significant professional factors, while the risks and the exposure to violence and the application of the additional payment based on the performance of candidates are the systemic factors that affect selections and preferences. Also, it was concluded that qualitative data obtained in the research were supported with quantitative data.
Keywords: Specialization Choice in Medicine; Specialization Branch Preferences in Medicine; Specialist Physicians; Mixed Research Design